2001
DOI: 10.1021/cc010010b
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Supported Benzotriazoles as Catalysts in the Synthesis of Tetrahydroquinolines by Condensation of Aldehydes with Aromatic Amines

Abstract: Four polymer-supported benzotriazoles were prepared by linkage of 5-(hydroxymethyl)benzotriazole and benzotrizaole-5-carboxylic acid with Wang resin, Merrifield resin, and (monomethoxy)poly(ethylene glycol). The solid-phase and liquid-phase syntheses of tetrahydroquinolines were achieved by two-pair coupling reactions of aldehydes and aromatic amines using these polymer-supported benzotriazoles as the promoters. The ether-type benzotriazole prepared by loading 5-(hydroxymethyl)benzotriazole onto Merrifield res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The development of a fast and sensitive colorimetric sensor or reagent for detection and identification of ions [1][2][3][4][5][6][7] and small molecules [8][9][10][11][12] has emerged as an actively investigated area of research in recent years. Aromatic amines are one of the most important compounds and are used widely, not only in the synthesis of drugs [13][14][15][16][17] and pesticides [18][19][20][21][22][23] as key structure units, but also in the field of polymer materials chemistry. [24][25][26][27][28] However, a number of aromatic amines have recently been found to be carcinogens [29][30][31][32][33] and have been polluting the human environment [34][35][36] including food and water.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a fast and sensitive colorimetric sensor or reagent for detection and identification of ions [1][2][3][4][5][6][7] and small molecules [8][9][10][11][12] has emerged as an actively investigated area of research in recent years. Aromatic amines are one of the most important compounds and are used widely, not only in the synthesis of drugs [13][14][15][16][17] and pesticides [18][19][20][21][22][23] as key structure units, but also in the field of polymer materials chemistry. [24][25][26][27][28] However, a number of aromatic amines have recently been found to be carcinogens [29][30][31][32][33] and have been polluting the human environment [34][35][36] including food and water.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have also reported the synthesis of stable nitrenium ions using BT as synthon [19]. Polymer-supported benzotriazoles were also used as catalysts for the generation of a tetrahydroquinoline library [20].…”
Section: Introductionmentioning
confidence: 99%
“…The use of organic molecules as catalysts has provided attractive alternatives to the more traditional metal‐catalyzed. In recent years, benzotriazole has wide application as a synthetic auxiliary in a multitude of synthetic endeavors , such as nitrogen ligand, reactive promotion reagents, or catalyst. But it has not been studied as a catalyst in the synthesis of imidazoles until now.…”
Section: Introductionmentioning
confidence: 99%